Composition and effects of inhalable size fractions of atmospheric aerosols in the polluted atmosphere. Part II. In vitro biological potencies - Novák, Jiří; Hilscherová, Klára; Landlová, Linda; Čupr, Pavel; Kohút, Lukáš; Giesy, John P; Klánová, Jana (Environment international, 2014)
Exposure to particulate matter (PM) in ambient air has been shown to lead to adverse health consequences. Six size fractions of PM with aerodynamic diameter smaller than 10μm (PM10) and gas phase were collected at six localities with different major pollution sources. Extracts of samples were assessed for AhR-mediated toxicity, (anti-)estrogenicity, (anti-)androgenicity and genotoxicity. The biological responses were interpreted relative to chemical characterization. Historically, for regulatory purposes, evaluation of air pollution was based mainly on assessment of the sum of PM10. In the case of AhR-mediated activity, PM1 was responsible for more than 75% of the activity of the particulate fraction from all localities. The assessed effects were correlated with concentrations of polycyclic aromatic hydrocarbons (PAH), organic carbon content and specific surface area of the PM. A significant proportion of biologically active chemicals seems to be present in the gas phase of air. The results suggest that an average daily exposure based just on the concentrations of contaminants contained in PM10, as regulated in EU legislation so far, is not a sufficient indicator of contaminants in air particulates and adoption of standards more similar to other countries and inclusion of other parameters besides mass should be considered.
Keywords: pevné částice; nádorové buněčné linie; DNA Damage; látky znečišťující vzduch; vystavení vlivu životního prostředí; Air Pollutants; Androgens; Atmosphere; androgeny; poškození DNA; Biological Assay; PM size fractions; aerosoly; Aerosols; Receptors, Aryl Hydrocarbon; Estrogenicity; Genotoxicity; Environmental Exposure; Cell Line, Tumor; polycyklické aromatické uhlovodíky; nadechnutí; Estrogen Receptor Modulators; Dioxin-like toxicity; Humans; Antiandrogenicity; modulátory estrogenních receptorů; Polycyclic Aromatic Hydrocarbons; Particulate Matter; biotest; Inhalation; receptory aromatických uhlovodíků; lidé; atmosféra